2007
DOI: 10.1177/153303460700600409
|View full text |Cite
|
Sign up to set email alerts
|

Technical Description, Phantom Accuracy, and Clinical Feasibility for Single-Session Lung Radiosurgery Using Robotic Image-Guided Real-time Respiratory Tumor Tracking

Abstract: To describe the technological background, the accuracy, and clinical feasibility for single session lung radiosurgery using a real-time robotic system with respiratory tracking. The latest version of image-guided real-time respiratory tracking software (Synchrony®, Accuray Incorporated, Sunnyvale, CA) was applied and is described. Accuracy measurements were performed using a newly designed moving phantom model. We treated 15 patients with 19 lung tumors with robotic radiosurgery (CyberKnife®, Accuray) using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…However, in a later publication, they reported a pneumothorax rate of 16% after the placement of 72 fiducials in 25 patients [26]. Muacevic et al reported a chest tube insertion in two patients out of 15 after fiducial implantation owing to pneumothorax [27]. Whyte et al reported three patients with pneumothoraces; two were managed expectantly but one required chest tube placement [28].…”
Section: Percutaneous Intrapulmonal Placementmentioning
confidence: 97%
“…However, in a later publication, they reported a pneumothorax rate of 16% after the placement of 72 fiducials in 25 patients [26]. Muacevic et al reported a chest tube insertion in two patients out of 15 after fiducial implantation owing to pneumothorax [27]. Whyte et al reported three patients with pneumothoraces; two were managed expectantly but one required chest tube placement [28].…”
Section: Percutaneous Intrapulmonal Placementmentioning
confidence: 97%
“…In the Munich Center 35 patients harbouring small (<50 cc) lung tumors have undergone this procedure using 24 Gy in a single session procedure ( Table 4). The preliminary results are very promising and no significant treatment-related toxicity was found [3]. However, follow-up is too short for definitive assessment of clinical outcome (Fig.…”
Section: Robotic Respiratory Motion Compensation For Body Treatmentsmentioning
confidence: 85%
“…Radiosurgical applications are evolving from standard neurosurgical indications (i.e., acoustic neurinomas, meningiomas, brain metastases, etc.) to extracranial indications [3]. Treating tumors of the lung, liver, kidney, etc., is particularly challenging because these organs are subject to respiratory movements.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the correlation between the position of the LEDs and the internal fiducials, a correlation model predicts the location of the tumor throughout the respiratory cycle and moves the treatment beam to remain on target with the treatment volume. The system has been shown in end-to-end phantom tests to be accurate to within 1.5 mm (Muacevic et al, 2007; Wong et al, 2007). …”
Section: Methodsmentioning
confidence: 99%